Uji Efektivitas Carboxymethyl Cellulose (CMC) dan Pektin sebagai Bahan Edible Coating Buah Stroberi: Review - Elisa Fitri (Universitas Muhammadiyah Semarang, 2023)
Carboxymethyl cellulose (CMC) and pectin are edible coating materials used to maintain the quality and shelf life of fruit. Strawberry is a non-climateric fruit with a short post-harvest shelf life and is easily damaged. This article aims to examine the shelf life of fruit, physical and chemical properties of fruit, to compare the effectiveness of using CMC and pectin as edible coating materials to maintain the quality and shelf life of strawberries. Articles were written in stages through a gradual library search through Publish or Perish and then continued with a more specific literature search through Google Scholar with the keywords